Genome-Wide Identification and Expression Profiling of DUF221 Gene Family Provides New Insights Into Abiotic Stress Responses in Potato - Zaynab, Madiha; Peng, Jiaofeng; Sharif, Yasir; Albaqami, Mohammed; Al-Yahyai, Rashid; Fatima, Mahpara; Nadeem, Muhammad Azhar; Khan, Khalid Ali; Alotaibi, Saqer S.; Alaraidh, Ibrahim A.; Shaikhaldein, Hassan O.; Li, Shuangfei (Frontiers in Plant Science, 2022)
The domain of the unknown function 221 (DUF221) proteins regulate several processes in plants, including development, growth, hormone transduction mechanism, and abiotic stress response. Therefore, a comprehensive analysis of the potato genome was conducted to identify the DDP proteins' role in potato. In the present study, we performed a genome-wide analysis of potato DUF221 genes, including phylogenetic inferences, chromosomal locations, gene duplications, gene structures, and expression analysis. In our results, we identified 10 DDP genes in the potato genome. The phylogenetic analysis results indicated that StDDPs genes were distributed in all four clades, and clade IV was the largest clade. The gene duplication under selection pressure analysis indicated various positive and purifying selection in StDDP genes. The putative stu-miRNAs from different families targeting StDDPs were also predicted in the present study. Promoter regions of StDDP genes contain different cis-acting components involved in multiple stress responses, such as phytohormones and abiotic stress-responsive factors. The analysis of the tissue-specific expression profiling indicated the StDDPs gene expression in stem, root, and leaf tissues. We subsequently observed that StDDP4, StDDP5, and StDDP8 showed higher expressions in roots, stems, and leaves. StDDP5 exhibited high expression against heat stress response, and StDDP7 showed high transcript abundance against salt stress in potato. Under abscisic acid (ABA) and indole acetic acid (IAA) treatments, seven StDDP genes' expressions indicated that ABA and IAA performed important roles in immunity response. The expression profiling and real-time qPCR of stems, roots, and leaves revealed StDDPs' significant role in growth and development. These expression results of DDPs are primary functional analysis and present basic information for other economically important crops.